Análisis a la tributación de las iglesias en colombia (2022)
The churches in Colombia have had an important meaning since the beginning of history, without a doubt they exercise a social work focused of the community. But according to what was proposed in this research, it has been possible to find the importance that the tax contribution by the churches has for the Colombian state, since evidencing the diversity of cults that are professed and the occupation they have in the territory national, it can be affirmed that in the development of their religious activity, the acquire great income, that although it is clear it is not about profits, through them large sums of money are moved, which are not under the observation of the entities of control. In times of change, today’s society demands that the churches should contribute to the country’s finances, as demonstrated in the survey presented, where they majority of those consulted think so. This research does not seek to affect the religious identity of the readers, rather it wants to show another vision different from that of faith, a vision from the tax area.